The Commonest Clinical Presentation of Gallstone Disease in Laparoscopically Cholecystectomized Patients - Khairallah Muzhir Gabash; Hawra Khairallah Muzhir (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cholelithiasis is the presence of one or more gallstones within the gallbladder. Gallstone disease is a common cause for surgical intervention all over the world.The objective of the study is to determine the order of frequency of clinical presentations for cholelithiasis in laparoscopically cholecystectomized patients in ALKarama teaching hospital.A total sample of 156 clearly documented gallstone disease and laparoscopic cholecystectomized patients were involved in the present study. In the current study, 156 laparoscopic cholecystectomized patients; (34) males and (122) females, ages range between 20 and 69 years with a mean (m=39.24±11.7). Common factors that justified the indication for laparoscopic cholecystectomy (LC) were found in the majority of patients with asymptomatic and mild GI presentation those factors include microlithiasis < 3mm, risk for gallbladder CA, history of bariatric surgery, coexistent morbidities like diabetes mellitus (DM) and hemolytic anemia (HA) or the LC was done in concomitant with another laparoscopic surgery.From the present study, we concluded that the mild GI symptoms represented by dyspepsia, nausea, flatulence and constipation, were at the top of clinical presentations for gallstone patients who underwent LC. The distribution of cases was higher in the 4th decade of life with female predominance.